2023
DOI: 10.3390/polym15061477
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Behavior of 3D-Printed Residue of Astragalus Particle/Poly(Lactic Acid) Biocomposites under Soil Conditions

Abstract: Astragalus is widely cultivated in China, and the residue of Astragalus particles (ARP) can be used as reinforcements in fused filament-fabricated (FFF) natural fiber/Poly(lactic acid)(PLA) biocomposites. To clarify the degradation behavior of such biocomposites, 3D-printed 11 wt% ARP/PLA samples were buried in soil, and the effects of soil burial duration on the physical appearance, weight, flexural properties, morphology, thermal stability, melting, and crystallization properties were investigated. At the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It was found that the sample lost its weight obviously with time: after being buried in soil for 180 days, the weight loss was 21.40%, indicating that the extension of soil-burial time would promote the biodegradation of ARP/TPS/PLA, which was consistent with the results from the visual appearance observation. Comparing the weight with that of pure PLA [ 21 ], it was found that ARP and TPS greatly accelerated the degradation of PLA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the sample lost its weight obviously with time: after being buried in soil for 180 days, the weight loss was 21.40%, indicating that the extension of soil-burial time would promote the biodegradation of ARP/TPS/PLA, which was consistent with the results from the visual appearance observation. Comparing the weight with that of pure PLA [ 21 ], it was found that ARP and TPS greatly accelerated the degradation of PLA.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous work, 11 wt.% was the best proportion for ARP to add into PLA for the FDM 3D printing of ARP/PLA pieces when the cost and quality of the filament were taken into consideration simultaneously [ 21 ]. In this paper, the maximum proportion of ARP in the composite was thus controlled within 11 wt.%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, biofilaments comprising PLA and CBSW at varying concentrations were developed and used to produce 3D models by FFF, offering a novel approach to waste recycling and reuse through FFF printing. The findings highlight the feasibility of integrating waste materials into the production cycle while emphasizing the importance of sustainable practices in modern manufacturing [ 22 , 23 , 24 , 25 ]. Based on this scenario, the aim of this study was to develop and characterize biocomposite filaments made from poly(lactic acid) and 5–10 wt.% of cocoa bean shell waste for FFF printing technology, from a CE perspective.…”
Section: Introductionmentioning
confidence: 99%